PENEMPATAN NARAPIDANA DI DALAM RUMAH TAHANAN DALAM KONTEKS SISTEM PENEGAKAN HUKUM PIDANA DI INDONESIA - Mita Yuyun Alina , R.B. Sularto, Purwoto (Diponegoro Law Journal, 2012)
Penitentiary is the estuary of penal justice system in Indonesia, a place where defendant has been found guilty by the court to imprisonment and the status changed to convict or if you are  already  living  in  the  penitentiary called  inmates.  Penitentiary’s purpose  is  to  train the inmates.  For  practicing  the  duty,  function  and  responsibility,  Penitentiary  works  based  on Undang-undang No, 12 tahun 1995. But in the practice, it’s not only Penitentiary’s duty to train the inmates but also House of Detention because many Penitentiaries are over capacity. Inmate placement in the House of Detention done just like in the Penitentiary as written in UU No. 12 tahun 1995. The practice of inmate training in the House of Detention, however is not written in the regulations. Caused by the over capacity in the Penitentiary, it is legal to do it in the House of  Detention. So that the officers would have double duty, to take care of the detainee and also train the inmates in the House of Detention. Inmate  placement  in  the  House  of  Detention  should  be  followed  with  completed facilities in proportion with the purposes. Because the structures and infrastructure in the House of Detention have many differences than in the Penitentiary.